Synthesis, Structure, and Properties of Binuclear Nickel(II) Complex with Hydrogen Bond and π···π Interaction - Li, Rong-Fang; Zhang, Xiao-Yu; Zhang, Tian; Feng, Xun; Liu, Xin-Fang (Asian Journal of Chemistry, 2015)
A binuclear nickel complex [Ni2(H3bptc)2(bpmp)(H2O)4]·2H2O (1) [H4bptc = biphenyl-2,3,3',5'-tetracarboxylic acid, bpmp = 1,4-bis(2-pyridylmethyl)pipyrazine] was obtained by hydrothermal reaction. Single crystal X-ray diffraction analysis shows that complex 1 crystallizes in triclinic space group P-1 with cell parameters a = 10.4630(11) Å, b = 10.9057(12) Å, c =13.3948(15) Å, a = 73.8070(10)°, b = 72.0600(10) °, g = 67.7310(10)°, V = 1322.6(2) Å3, Mr = 593.18, Z = 2, R1 = 0.0418, and wR2 = 0.1056. In complex 1, both Ni ions are six-coordinated to form slightly distorted octahedral coordination geometry. The binuclear symmetric nickel(II) unit containing main ligand H3bptc– and auxiliary ligand bpmp is further extended via hydrogen bonds and p···p interactions (d = 3.8454 Å) into a 3D supramolecular structure. In addition, complex 1 is also characterized by elemental analyses, IR spectra and thermogravimetric analyses.